Pilihan Rasional Muslimah Generasi Z dalam Konsumsi K-Drama Korea Selatan - Indah Puspita Sari (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2026)
The popularity of K-dramas in Indonesia is increasing because they present interesting, emotional, and meaningful storylines. One group that is a loyal fan of K-dramas is Muslim women generation Z, namely Muslim women born between 1997 and 2012. Muslim women Gen Z have wide access to various online viewing platforms and are adept at utilizing technology for entertainment and information needs. The purpose of this journal is to find out the reasons why Muslim women gen Z watch K-dramas and then analyze them using James S. Coleman's rational choice theory. The method used is a qualitative method with data collection in the form of literature studies, namely reviewing written sources such as journals and books and using interview techniques to gather information related to the reasons why Muslim women gen Z watch K-dramas. The results, the reasons why Muslim women gen Z watch K-dramas are for entertainment as a stress reliever, interested in Korean culture and visualization of Korean people and as a medium for education and self-reflection. In conclusion, Gen Z Muslim women's choice to watch K-Drama is the result of rational consideration of the benefits obtained, such as quality entertainment, cultural insight, and life values that can be internalized, so that it is in line with the concept of rational choice theory which emphasizes actions based on logical and conscious calculations of profit and loss.